Surface modification strategies for chrysin-loaded iron oxide nanoparticles to boost their anti-tumor efficacy in human colon carcinoma cells - Karimova, Aynura; Hajizada, Sabina; Shirinova, Habiba; Nuriyeva, Sevinj; Gahramanli, Lala; Yusuf, Mohammed Mohiuddin; Bellucci, Stefano; Reißfelder, Christoph; Yagublu, Vugar (Journal of Functional Biomaterials, 2024)
Enhancing nanoparticles’ anti-cancer capabilities as drug carriers requires the careful adjustment of formulation parameters, including loading efficiency, drug/carrier ratio, and synthesis method. Small adjustments to these parameters can significantly influence the drug-loading efficiency of nanoparticles. Our study explored how chitosan and polyethylene glycol (PEG) coatings affect the structural properties, drug-loading efficiency, and anti-cancer efficacy of Fe3O4 nanoparticles (NPs). The loading efficiency of the NPs was determined using FTIR spectrometry and XRD. The quantity of chrysin incorporated into the coated NPs was examined using UV-Vis spectrometry. The effect of the NPs on cell viability and apoptosis was determined by employing the HCT 116 human colon carcinoma cell line. We showed that a two-fold increase in drug concentration did not impact the loading efficiency of Fe3O4 NPs coated with PEG. However, there was a 33 Å difference in the crystallite sizes obtained from chitosan-coated Fe3O4 NPs and drug concentrations of 1:0.5 and 1:2, resulting in decreased system stability. In conclusion, PEG coating exhibited a higher loading efficiency of Fe3O4 NPs compared to chitosan, resulting in enhanced anti-tumor effects. Furthermore, variations in the loaded amount of chrysin did not impact the crystallinity of PEG-coated NPs, emphasizing the stability and regularity of the system.